2015
DOI: 10.1071/rd13234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary administration of letrozole and tamoxifen on gonadal development, sex differentiation and biochemical changes in common carp (Cyprinus carpio L.)

Abstract: The effect of letrozole and tamoxifen on the specific growth rate (SGR; % day(-1)), gonado-somatic index (GSI), total haemoglobin (g%), gonadal and serum protein as well as lipid, sex differentiation and 17β-oestradiol levels were studied in sexually undifferentiated Cyprinus carpio fingerlings 30 days post fertilisation (30 dpf) for 60 days. Results showed decreased GSI with tamoxifen treatment whereas letrozole increased it. There were reduced protein, lipid, triglyceride and cholesterol levels after treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Although no significant vitellogenin induction was observed, there was significant suppression of spermatogenesis in 50% and 100% EFF-exposed fish after 28 d of exposure and a nonsignificant trend for dose-dependent suppression of spermatogenetic activity in EFF-exposed fish after 14 d (Figure 4). Although the reproductive response to environmental estrogens has not been studied previously in Murray rainbowfish, spermatogenesis in fish is sensitive to diverse environmental contaminants, including estrogenic and anti-estrogenic EACs [7,60]. The inhibition of gonadal function observed in this experiment may be related to the strong anti-estrogenic activity of the WWTP effluent detected by the in vitro yeast estrogen screen assay, and suggests that even the effluent from an advanced WWTP may adversely impact fish reproductive health.…”
Section: Biological Effects and Implicationsmentioning
confidence: 73%
“…Although no significant vitellogenin induction was observed, there was significant suppression of spermatogenesis in 50% and 100% EFF-exposed fish after 28 d of exposure and a nonsignificant trend for dose-dependent suppression of spermatogenetic activity in EFF-exposed fish after 14 d (Figure 4). Although the reproductive response to environmental estrogens has not been studied previously in Murray rainbowfish, spermatogenesis in fish is sensitive to diverse environmental contaminants, including estrogenic and anti-estrogenic EACs [7,60]. The inhibition of gonadal function observed in this experiment may be related to the strong anti-estrogenic activity of the WWTP effluent detected by the in vitro yeast estrogen screen assay, and suggests that even the effluent from an advanced WWTP may adversely impact fish reproductive health.…”
Section: Biological Effects and Implicationsmentioning
confidence: 73%
“…Tmx has been recommended for use as a reference compound in fish testing in terms of understanding the potential impact of selective estrogen receptor modulators (SERMs) in aquatic life (Ankley et al, 2002). Previous studies in fish have analyzed the impact of dietary Tmx in fish reproduction (Mandiki et al, 2005;Singh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have reported interactions between temperature and steroids, with resulting effects on amphibian larval growth, development, and metamorphosis (Hayes, Chan & Licht, 1993); however, the effects of these interactions on amphibian sex development have rarely been assessed. Aromatase inhibitors do not exist in nature, but they have become more widely used in recent years because they can affect the levels of endogenous steroid hormones and are associated with better hormonal regulation than exogenous steroid hormones (Miyata & Kubo, 2000;Olmstead et al, 2009;Shen et al, 2013;Singh et al, 2015). Given the state of research on aromatase inhibitors and the potential effects of steroids on anuran larval growth and development, an investigation of the interactive effects of temperature and aromatase inhibitors on growth and sex development is warranted.…”
Section: Introductionmentioning
confidence: 99%